Effect of Some Polyphenolic Compounds on Biochemical Parameters in Leukemic Patients - Al-Taie, Wafa F.; Turki, Kismat M.; AL-Rubaie, Zeinab M. (Journal of the Faculty of Medicine Baghdad, 2016)
ackground :Polyphenolic compounds are groups of naturally occurring compounds in different plants. They are promising product to protect, and prevent leukemia and many types of cancer by different mechanisms. Objectives: The present study designed to study the effect of polyphenolic compounds [Ellagic acid (EA), Tannic acid (TA) and Caffiec acid (CA)] on GOT,GPT activities and total protein TP concentration in all types of leukemia [acute myeloblastic leukemia (AML), acute lymphoblastic leukemia (ALL), chronic myeloblasti leukemia (CML) and chronic lymphoblastic leukemia (CLL)],in addition to compare the potency of these compounds among each other. Patients and Methods: Blood samples were collected from a hundred leukemic patients. In addition fifty healthy subjects age matched were chosen as control group. Transaminases (GOT and GPT) activities and total protein concentration in sera of all studied groups were determined before and after addition of 10 mM (EA, TA and CA) Results: There is a significant increase in serum GOT,GPT activity and TP concentration for all leukemic groups compared to control. The elevated values of GOT, GPT activities and TP concentration in patients were returned to about normal values in most cases after addition of 10 mM (EA, TA and CA). Conclusion: Results showed the effectiveness of polyphenolic compounds (EA, TA and CA) in treatment of leukemia in vitro study , also, results revealed that EA was the most potent compound among the types of polyphenolic compounds studied in affecting the parameters to be close to normal values.